Effect of Magnet Thickness and Width Variation on Back EMF of 18-Slot 16-Pole Permanent Magnet Synchronous Generator - Darmawan, Isra' Nuur; Abidin, Asroful; Ramadhan, Muhammad Afif Makruf; Rizki, Achmad (Applied Engineering, Innovation, and Technology, 2024)
Permanent magnet synchronous generators (PMSG) converts mechanical energy into electrical energy through electromagnetic induction, with the excitation field generated by permanent magnets instead of coils. This paper investigates the effects of varying magnet thickness and width on the back electromotive force (back EMF) of an 18-slot 16-pole PMSG using finite element method (FEM) simulations. The aim is to understand how these geometric parameters influence the back EMF values, which are crucial for generator design and performance evaluation. The FEM modelling results show that a 5 mm magnet thickness yields the highest back EMF value of 130.47 V, while a 15 mm magnet width produces a back EMF of 100.65 V. Additionally, the back EMF constant (KE) is maximized at 0.79 V·s/rad for a 5 mm magnet thickness and 0.55 V·s/rad for a 15 mm magnet width. These findings provide insights into optimising magnet dimensions for improving the efficiency and output characteristics of PMSGs in various applications.